Upaya Peningkatan Hasil Belajar Biologi Siswa Kelas X Menggunakan Model Pembelajaran Student Acilitator And Explaining - Merti Triyanti; Usman Nulhakim (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2018)
The purpose of this study was to determine the improvement in biology learning outcomes of class X students of SMA 7 Lubuklinggau by applying the student facilitator and explaining learning model. This research is Classroom Action Research (CAR), which is a study consisting of 2 cycles where each cycle consists of four steps: planning, implementing, observing, and reflecting. Data collection was carried out with the teacher activity observation sheet and the daily test sheet. The subjects of this study were 38 students of class X in SMA Negeri 7 Lubuklinggau. From the research results it is known that by applying the student facilitator and explaining learning model, students who reach KKM from 52.88% in the first cycle to 86.21% in the second cycle. Based on the analysis of these data it can be concluded that by applying the learning facilitator and explaining learning model the quality of learning in Biology subjects in class X SMA Negeri 7 Lubuklinggau increases. The magnitude of the increase in student learning outcomes in class X SMA Negeri 7 Lubuklinggau on biology learning using the student facilitator and explaining learning model by 33.33%. Conclusion, an increase in biology learning outcomes of class X students of SMA Negeri 7 Lubuklinggau by applying the student facilitator and explaining learning model. Keywords: biology learning outcomes, student facilitator and explaining